2021
DOI: 10.1186/s13068-021-01915-z
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptional response to drought stress among bioenergy grass Miscanthus species

Abstract: Background Miscanthus is a commercial lignocellulosic biomass crop owing to its high biomass productivity, resilience and photosynthetic capacity at low temperature. These qualities make Miscanthus a particularly good candidate for temperate marginal land, where yields can be limited by insufficient or excessive water supply. Differences in response to water stress have been observed among Miscanthus species, which correlated to origin. In this study, we compared the physiological and molecular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Other quantified free amino acids revealed substantial stress-induced changes in their contents. Among those reporting a large increment, serine (Ser) was second only to Pro in its increase (Figure 3a), contrary to the reported downregulation of Ser metabolism in miscanthus leaves under drought, by De Vega et al (2021) transcriptomics analyses. This could be a form of a negative feedback control to reverse its stress-induced accumulation to almost toxic levels.…”
Section: Vacuolar Osmotic Adjustmentmentioning
confidence: 59%
See 2 more Smart Citations
“…Other quantified free amino acids revealed substantial stress-induced changes in their contents. Among those reporting a large increment, serine (Ser) was second only to Pro in its increase (Figure 3a), contrary to the reported downregulation of Ser metabolism in miscanthus leaves under drought, by De Vega et al (2021) transcriptomics analyses. This could be a form of a negative feedback control to reverse its stress-induced accumulation to almost toxic levels.…”
Section: Vacuolar Osmotic Adjustmentmentioning
confidence: 59%
“…Accordingly, exploiting M. sinensis ample genetic diversity via comparative studies, is pivotal in screening for better performing genotypes and the consequent breeding efforts toward improved tolerance in this crop (Weng et al, 2022). This was evident in the dissimilar impact of water-deficiency (Van Der Weijde et al, 2017b) and salt (Chen et al, 2017) on diverse populations of M. sinensis genotypes, and likewise the differential expression of common regulatory pathways after flooding and drought treatments (De Vega et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the phenylpropanoid biosynthesis (ko00940), as a stress-resistant pathway [ 68 ], was enriched in the KEGG analysis, while the contents of lignin and CAD activities were significantly changed ( Figure 9 ). In addition, the three pathways have been reported to participate in responding to abiotic stress in Hibiscus cannabinus , Miscanthus and tomato ( Solanum lycopersicum ) [ 69 , 70 , 71 ]. Our study demonstrated the mechanisms underlying the drought stress responses by tiger nuts, which enhances drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that in the case of energy crops, the yield is mainly determined by the water factor, in the case of water shortage, the cultivation of plantations becomes economically unjustified. Therefore, it is important to recognize the impact of water deficit on plant growth and development [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%